2010
DOI: 10.1007/s10295-010-0722-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of mulberroside A from Morus alba results in enhancement of tyrosinase inhibition

Abstract: Mulberroside A, a glycosylated stilbene, was isolated and identified from the ethanol extract of the roots of Morus alba. Oxyresveratrol, the aglycone of mulberroside A, was produced by enzymatic hydrolysis of mulberroside A using the commercial enzyme Pectinex. Mulberroside A and oxyresveratrol showed inhibitory activity against mushroom tyrosinase with an IC(50) of 53.6 and 0.49 microM, respectively. The tyrosinase inhibitory activity of oxyresveratrol was thus approximately 110-fold higher than that of mulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 30 publications
0
43
0
1
Order By: Relevance
“…Oxyresveratrol and mulberroside A have displayed antioxidant, anti-inflammatory, and anti-browning activities, those of oxyresveratrol being much greater than mulberroside A 10,25 . We previously reported that oxyresveratrol inhibits mushroom tyrosinase via a mixed inhibition with l-tyrosine as a substrate, resulting in approximately 110-fold more inhibition than mulberroside A 17 . Following oral administration, mulberroside A is metabolized in the liver or digestive tract, resulting in an almost complete conversion to oxyresveratrol, which is easily transported in tissue 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxyresveratrol and mulberroside A have displayed antioxidant, anti-inflammatory, and anti-browning activities, those of oxyresveratrol being much greater than mulberroside A 10,25 . We previously reported that oxyresveratrol inhibits mushroom tyrosinase via a mixed inhibition with l-tyrosine as a substrate, resulting in approximately 110-fold more inhibition than mulberroside A 17 . Following oral administration, mulberroside A is metabolized in the liver or digestive tract, resulting in an almost complete conversion to oxyresveratrol, which is easily transported in tissue 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxyresveratrol also did not show stronger inhibitory activity than mulberroside A on melanin synthesis in S. bikiniensis. The 50% inhibition concentration (IC 50 ) values of mulberroside A and oxyresveratrol were 53.6 µM and 0.49 µM, respectively, with L-tyrosine as the substrate 17 . The relative in vitro activities of mushroom tyrosinase using L-DOPA as a substrate were 73.9% and almost 100% with treatment of 5 µM oxyresveratrol or 5 µM mulberroside A, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24,[30][31][32][33][34] Because the deglucosylated form of hydroxystilbene has more potent tyrosinase inhibitory activity than its glucosylated form, 22,35) the biotransformation of stilbene glycoside to an aglycone has been performed using commercial deglycosylation enzyme products such as cellulase and Pectinex Ò . 22,36) Although these products are used widely as hydrolyzing enzymes, we reasoned that a biotransformation process based on microbial fermentation without a purification process of enzyme sources might represent a more convenient and economical method for the industrial production of bioactive herbal extracts. Therefore, suitable microbial strains were investigated to identify the most efficient organism for the biotransformation of the MA in MCR extract to OXY.…”
Section: Differences In the Bioconversion Patterns Of Ma Under Treatmmentioning
confidence: 99%
“…19) Moreover, OXY showed approximately 110-fold higher tyrosinase inhibitory activity than did MA against L-tyrosine substrate. 22) Flavonoids generally exist in glycosylated form in plant and food sources, and upon ingestion are absorbed after conversion into deglycosylated aglycones by intestinal enzymes and/or gut microbial enzymes. Flavonoid aglycones exhibit improved bioavailability and greater bioactivity than the respective glycosidic forms.…”
mentioning
confidence: 99%